GAMBARAN TINGKAT PENGETAHUAN ORANGTUA TERHADAP PENDIDIKAN ANAK USIA DINI DI WILAYAH KELURAHAN BENDAN KOTA PEKALONGAN - Suryo Pratikwo; Sri Mawar; Sirly Amri Meilynda (JURNAL LITBANG KOTA PEKALONGAN, 2016)
EARLY CHILDHOOD EDUCATION (ECE) IS AN EFFORT OF THE COACHING FOR CHILDREN FROM BIRTH TO SIX YEARS OLD DONE BY GIVING EDUCATION STIMULUS IN ORDER TO HELP THE GROWTH AND DEVELOPMENT OF PHYSICAL AS WELL AS SPIRITUAL SO THE CHILDREN HAVE A PREPARATION IN READINESS ENROLLING FURTHER EDUCATION. THE EFFECT OR PROBLEMS WILL APPEAR IF THE MOTHER HAS LACK OF UNDERSTANDING ABOUT ECE IS THE MOTHER DOES NOT KNOW HOW TO STIMULATE THE CHILDREN PROPERLY AND ALSO MOTHERS DON'T UNDERSTAND ABOUT THE PROPER NURTURING, IT CAN HAPPEN ESPECIALLY FOR MOTHERS WHO HAVE A CHILD FOR FIRST TIME THEY ARE WORKING MOTHERS. THE PURPOSE OF THIS RESEARCH IS TO KNOW THE DESCRIPTION OF THE MOTHER'S KNOWLEDGE ABOUT EARLY CHILDHOOD EDUCATION (ECE) IN THE REGION OF THE BENDAN VILLAGE PEKALONGAN. THIS TYPE OF RESEARCH USES DESCRIPTIVE METHOD WITH THE TYPE OF RESEARCH SURVEY. SAMPLING TECHNIQUE BASED ON RANDOM SAMPLING OF A POPULATION OF MOTHERS WHO HAVE CHILDREN AGED 0-5 YEARS WITH A TOTAL OF 86 RESPONDENTS. INSTRUMENT USING A QUESTIONNAIRE. THE RESEARCH RESULTS OBTAINED FOR MOTHERS WHO HAVE CHILDREN AGED 0-5 YEARS IN THE AREA BENDAN VILLAGE ARE HAVING SUFFICIENT KNOWLEDGE ENOUGH ABOUT EARLY CHILDHOOD EDUCATION (ECE), NAMELY 65,12 (56%). ADVICE FOR MOTHERS WHO HAVE CHILDREN AGED 0-5 YEARS IS TO BE EXPECTED TO ENHANCE HIS KNOWLEDGE AND ACTIVELY MORE SEEKING INFORMATION ABOUT EARLY CHILDHOOD EDUCATION AND HERE ALSO EXPECTED SO THAT THE ECE INSTITUTIONS CAN PROVIDE BETTER INFORMATION ABOUT ECE.